2024
DOI: 10.1080/22221751.2024.2321992
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility of geographically distinct Ixodes ricinus populations to tick-borne encephalitis virus and louping ill virus

Julian W. Bakker,
Helen J. Esser,
Hein Sprong
et al.

Abstract: Tick-borne encephalitis virus (TBEV) is an emerging pathogen in the Netherlands. Multiple divergent viral strains are circulating and the focal distribution of TBEV remains poorly understood. This may, however, be explained by differences in the susceptibility of tick populations for specific viruses and viral strains, and by viral strains having higher infection success in their local tick population. We investigated this hypothesis by exposing Dutch Ixodes ricinus ticks to two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Experimental studies of POWV in ticks have been performed in Dermacentor variab [23,24], Haemaphysalis longicornis [25], Amblyomma americanum [24], and I. scapularis [24,2 Notably, these studies have relied on the use of highly passaged historical virus stra Importantly, it has been shown that I. ricinus ticks have different levels of susceptibility genetically distinct TBEV strains, demonstrating a potential impact of virus genotype tick infection [27]. With the emergence of POWV in North America, the use of low-p sage, contemporary, genetically, and geographically diverse isolates is essential for an curate representation of tick transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies of POWV in ticks have been performed in Dermacentor variab [23,24], Haemaphysalis longicornis [25], Amblyomma americanum [24], and I. scapularis [24,2 Notably, these studies have relied on the use of highly passaged historical virus stra Importantly, it has been shown that I. ricinus ticks have different levels of susceptibility genetically distinct TBEV strains, demonstrating a potential impact of virus genotype tick infection [27]. With the emergence of POWV in North America, the use of low-p sage, contemporary, genetically, and geographically diverse isolates is essential for an curate representation of tick transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The large differences in transstadial transmission rates in these studies may be explained by the differences in physiological conditions of these ticks. Infection success of viruses in ticks after an infectious bloodmeal is influenced by tick origin and collection date [ 30 , 57 ]. Moreover, microbiota of arthropods differ between laboratory-reared and field-collected specimens [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…An artificial membrane blood-feeding system was adapted from Oliver et al [ 28 ] and Krull et al [ 29 ] with several modifications as described in [ 30 ]. The blood-feeding unit consisted of a polycarbonate tube (50 x 30 x 2 mm, Flexinplex kunstoffen, the Netherlands) glued to a silicon membrane and closed with a cultivation plug for Drosophila .…”
Section: Methodsmentioning
confidence: 99%